2008
DOI: 10.1016/j.cognition.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Ordered short-term memory differs in signers and speakers: Implications for models of short-term memory

Abstract: Capacity limits in linguistic short-term memory (STM) are typically measured with forward span tasks in which participants are asked to recall lists of words in the order presented. Using such tasks, native signers of American Sign Language (ASL) exhibit smaller spans than native speakers ([Boutla, M., Supalla, T., Newport, E. L., & Bavelier, D. (2004). Short-term memory span: Insights from sign language. Nature Neuroscience, 7(9), 997-1002]). Here, we test the hypothesis that this population difference reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 63 publications
(90 reference statements)
4
52
4
2
Order By: Relevance
“…These findings support and extend previous behavioural findings showing that sign language users, both deaf and hearing do not process order information in WM in the same Temporal organization in WM 19 way as hearing non-signers (Bavelier, Newport et al, 2008;Boutla, Supalla, Newport & Bavelier, 2004;Geraci, Gozzi, Papagno & Cecchetto, 2008;Marschark & Mayer, 1998;O'Connor & Hermelin, 1973;1976;Rönnberg et al, 2004;Rudner & Rönnberg, 2008a;Wilson, Bettger, Niculae & Klima, 1997;Wilson & Emmorey, 2003) The neuroimaging literature has also shown that although WM for sign language in both hearing (Rönnberg et al, 2004) and deaf (Bavelier, Newman et al, 2008;Buchsbaum et al, 2005;Pa, Wilson, Pickell, Bellugi & Hickok, 2008) signers is supported by neural networks similar to those in hearing non-signers, there is net engagement of the superior parietal cortex bilaterally for WM for sign language (Bavelier, Newman et al, 2008;Rönnberg et al, 2004) which may be related to retrieval processes (Bavelier, Newman et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings support and extend previous behavioural findings showing that sign language users, both deaf and hearing do not process order information in WM in the same Temporal organization in WM 19 way as hearing non-signers (Bavelier, Newport et al, 2008;Boutla, Supalla, Newport & Bavelier, 2004;Geraci, Gozzi, Papagno & Cecchetto, 2008;Marschark & Mayer, 1998;O'Connor & Hermelin, 1973;1976;Rönnberg et al, 2004;Rudner & Rönnberg, 2008a;Wilson, Bettger, Niculae & Klima, 1997;Wilson & Emmorey, 2003) The neuroimaging literature has also shown that although WM for sign language in both hearing (Rönnberg et al, 2004) and deaf (Bavelier, Newman et al, 2008;Buchsbaum et al, 2005;Pa, Wilson, Pickell, Bellugi & Hickok, 2008) signers is supported by neural networks similar to those in hearing non-signers, there is net engagement of the superior parietal cortex bilaterally for WM for sign language (Bavelier, Newman et al, 2008;Rönnberg et al, 2004) which may be related to retrieval processes (Bavelier, Newman et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…These include less prominent temporal organization (Bavelier, Newport, Hall, Supalla & Boutla, 2008;Rudner & Rönnberg, 2008a;Wilson, Bettger, Niculae & Klima, 1997) and engagement of additional neural structures in the superior parietal regions, suggesting a greater reliance on spatial processing for WM for sign Temporal organization in WM 7 language compared to WM for speech (Rönnberg et al, 2004;Rudner et al, 2007), possibilypossibly related to retrieval mechanisms (Bavelier, Newman et al, 2008).…”
Section: Modality Specific Aspects Of Working Memorymentioning
confidence: 99%
“…While the average forwards digit span for hearing adults using a spoken language is 7 +/-2, for Deaf and hearing adults using a signed language this is significantly lower, at around 5 +/-1 (Boutla, Supalla, Newport & Bavelier, 2004;Bavelier, Newport, Hall, Supalla & Boutla, 2006). However, although signers are unable to remember as many items in sequence as speakers are, they are able to recall the same number of items when their exact sequence is not required (Bavelier, Newport, Hall, Supalla & Boutla, 2008). Hence it appears that sequence is important for PWM in spoken languages, but that sequentiality does not play as great a role in signers' PWM (Bavelier et al, 2008;Geraci, Gozzi, Papagno & Cecchetto, 2008).…”
Section: Phonological Working Memorymentioning
confidence: 97%
“…However, although signers are unable to remember as many items in sequence as speakers are, they are able to recall the same number of items when their exact sequence is not required (Bavelier, Newport, Hall, Supalla & Boutla, 2008). Hence it appears that sequence is important for PWM in spoken languages, but that sequentiality does not play as great a role in signers' PWM (Bavelier et al, 2008;Geraci, Gozzi, Papagno & Cecchetto, 2008). This conclusion therefore raises the possibility that digit span is not a fair measure of PWM in signers, and that a nonsense sign repetition test, because it takes into account the greater degree of simultaneity in sign language structure, would have more validity.…”
Section: Phonological Working Memorymentioning
confidence: 99%
“…For example, they have poorer skills than hearing individuals on arithmetic operations such as multiplication (Nunes et al, 2009) and fractions (Titus, 1995), relational statements (Kelly, Lang, Mousley, & Davis, 2003) and digit-based short-term memory (STM; Bavelier, Newport, Hall, Supalla, & Boutla, 2008;M. Wilson, Bettger, Niculae, & Klima, 1997).…”
Section: IImentioning
confidence: 99%